A novel small molecule inhibitor of human Drp1 - Ayeshah A. Rosdah; Belinda M. Abbott; Christopher G. Langendorf; Yali Deng; Jia Q. Truong; Helen M. M. Waddell; Naomi X. Y. Ling; William J. Smiles; Lea M. D. Delbridge; Guei-Sheung Liu; Jonathan S. Oakhill; Shiang Y. Lim; et al. (Scientific Reports, 2022)
Abstract Mitochondrial dynamin-related protein 1 (Drp1) is a large GTPase regulator of mitochondrial dynamics and is known to play an important role in numerous pathophysiological processes. Despite being the most widely used Drp1 inhibitor, the specificity of Mdivi-1 towards human Drp1 has not been definitively proven and there have been numerous issues reported with its use including off-target effects. In our hands Mdivi-1 showed varying binding affinities toward human Drp1, potentially impacted by compound aggregation. Herein, we sought to identify a novel small molecule inhibitor of Drp1. From an initial virtual screening, we identified DRP1i27 as a compound which directly bound to the human isoform 3 of Drp1 via surface plasmon resonance and microscale thermophoresis. Importantly, DRP1i27 was found to have a dose-dependent increase in the cellular networks of fused mitochondria but had no effect in Drp1 knock-out cells. Further analogues of this compound were identified and screened, though none displayed greater affinity to human Drp1 isoform 3 than DRP1i27. To date, this is the first small molecule inhibitor shown to directly bind to human Drp1.